The Influence Of The Trend Of Childbirth Using The Blowing Method With Perineal Rupture Incidents At TPMB Ika Fatmawati In 2022 - Fatmawati, Ika; Nursitiyaroh, Nursitiyaroh (International Journal of Health and Pharmaceutical (IJHP), 2023)
Background: The trend of giving birth using the blowing method is used in a repetitive pattern for breathing exercises. There are many advantages of this steady, rhythmic breathing pattern during labor one of which is that the abdominal cavity can grow in size as a result of the increased relaxation of the abdominal muscles caused by breathing exercises. Purpose of Writing: To Influence the Trend of Childbirth Using the Blowing Method with Perineal Rupture Events at TPMB Ika Fatmawati in 2022. Research Methods: In this study, it was an experimental (quasi-experimental) design with The Nonrandomized Control Group Pretest Posttest Design with a quantitative approach. Sampling in this study is the total sampling of 30 people. divided into 2 groups, namely 15 people in the intervention group and 15 people in the control group. The sampling technique used was a strategy to identify the sample by taking respondents who happened to be available or the time available at the location according to the needs of the study. The inclusion criteria were women who gave birth normally, while the exclusion criteria were TBBJ counts of more than 3800 grams. Results: Results of statistical test analysis independent sample t test obtained Asymp. Sig (2 – Talled), namely 0.004 < α (0.05) it can be concluded that there is an influence of the trend of blowing births with perineal rupture events at TPMB Ika Fatmawati in 2022. Conclusions and suggestions: The results of this study are expected that midwives can carry out the trend of giving birth by blowing and making the mother's mood calm so that it can reduce the incidence of perineal rupture.